Targeting IFN activity to both B cells and plasmacytoid dendritic cells induces a robust tolerogenic response and protection against EAE - Anje Cauwels (Nature Portfolio, 2021)
Abstract Type I Interferon (IFN) was the very first drug approved for the treatment of Multiple Sclerosis (MS), and is still frequently used as a first line therapy. However, systemic IFN also causes considerable side effects, affecting therapy adherence and dose escalation. In addition, the mechanism of action of IFN in MS is multifactorial and still not completely understood. Using AcTaferons (Activity-on-Target IFNs, AFNs), optimized IFN-based immunocytokines that allow cell-specific targeting, we have previously demonstrated that specific targeting of IFN activity to dendritic cells (DCs) can protect against experimental autoimmune encephalitis (EAE), inducing in vivo tolerogenic protective effects, evidenced by increased indoleamine-2,3-dioxygenase (IDO) and transforming growth factor β (TGFβ) release by plasmacytoid (p) DCs and improved immunosuppressive capacity of regulatory T and B cells. We here report that targeting type I IFN activity specifically towards B cells also provides strong protection against EAE, and that targeting pDCs using SiglecH-AFN can significantly add to this protective effect. The superior protection achieved by simultaneous targeting of both B lymphocytes and pDCs correlated with improved IL-10 responses in B cells and conventional cDCs, and with a previously unseen very robust IDO response in several cells, including all B and T lymphocytes, cDC1 and cDC2.